Overexpression of mTOR in Leukocytes from ALS8 Patients - Gomes, Nathália A.; das Chagas Lima e Silva, Francisco; de Oliveira Volpe, Caroline Maria; Villar-Delfino, Pedro Henrique; de Sousa, Camila Ferreira; Rocha-Silva, Fabiana; Nogueira-Machado, José Augusto (Current Neuropharmacology, 2023)
Background: The mutated VAPBP56S (vesicle B associated membrane protein – P56S) protein has been described in a Brazilian family and classified as Amyotrophic Lateral Sclerosis type 8 (ALS8). Objective: We aimed to study altered biochemical and immunological parameters in cells from ALS8 patients to identify possible biomarkers or therapeutic targets. Methods: Wild-type VAPB, VAPBP56S, mTOR, proinflammatory cytokines, and oxidant/reducing levels in serum, leucocytes, and cellular lysate from ALS8 patients and health Controls were performed by ELISA, fluorimetry, and spectrophotometry. Results: Our results showed similar levels of mutant and wild-type VAPB in serum and intracellular lysate (p > 0.05) when ALS8 patients and Controls were compared. IL-1β, IL-6, and IL-18 levels in patients and Controls showed no difference, suggesting an absence of peripheral inflammation (p > 0.05). Oxidative metabolic response, assessed by mitochondrial ROS production, and reductive response by MTT reduction, were higher in the ALS8 group compared to Controls (p < 0.05), although not characterizing typical oxidative stress in ALS8 patients. Total mTOR levels (phosphorylated or non-phosphorylated) of ALS8 patients were significantly lower in serum and higher in intracellular lysate than the mean equivalents in Controls (p < 0.05). A similar result was observed when we quantified the phosphorylated protein (p < 0.05). Conclusion: We demonstrate the possibility of using these biochemical and immunological parameters as potential therapeutic targets or biomarkers. Furthermore, by hypothesis, we suggest a hormetic response in which both VAPB forms could coexist in different proportions throughout life. The mutated VAPBP56S production would increase with aging and predominate over the wild-type VAPB levels, determining the onset of symptoms and aggravating the disease.
Keywords: ROS